2005
DOI: 10.1159/000086995
|View full text |Cite
|
Sign up to set email alerts
|

Study of Tobacco Habits and Alterations in Enzymatic Antioxidant System in Oral Cancer

Abstract: Aim and Objective: Tobacco is a major etiological factor for oral cancer development, accounting 30–40% of all cancer cases in India. Tobacco consumption generates free radicals and causes oxidative damages. In order to counteract these lethal effects, normal living cells have multiple antioxidant defense systems in a cascade manner. Thus, it seems that studying biological parameters, like antioxidant enzyme system, may be helpful in risk assessment and early diagnosis of oral cancer. Therefore, we analyzed er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 57 publications
3
37
0
2
Order By: Relevance
“…7 Tobacco consumption causes oral cancers, 30-40% of cancer cases accounted in India. 8 It is also generates increased oxidative stress and lipid peroxidation (LPO). The gas phase of CS contains free radicals such as superoxide radicals, hydroxyl radicals and hydrogen peroxide (H2O2) turn to causes oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Tobacco consumption causes oral cancers, 30-40% of cancer cases accounted in India. 8 It is also generates increased oxidative stress and lipid peroxidation (LPO). The gas phase of CS contains free radicals such as superoxide radicals, hydroxyl radicals and hydrogen peroxide (H2O2) turn to causes oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Tobacco consumption produces free radicals; it also increased oxidative stress and LPO. 8 Oxidative effects via free radical generation in smokers' cause LPO, oxidation of proteins and damage to tissues mainly that of lung. The antioxidant enzymes superoxide dismutase (SOD) catalyses the dismutation of superoxide anions (O2) to hydrogen peroxide (H2O2), and glutathione peroxidase (GPx), catalase (CAT) catalyzes the degradiation affected by CS resulting in deleterious effects.…”
Section: Introductionmentioning
confidence: 99%
“…reactive oxygen species cause loss of salivary antioxidant capacity lead development of oral cancer in many tobacco chewers and smokers [4,5]. Antioxidants, on the other hand have a protective role by scavenging the free radicals [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is scant medical literature on this subject. Although a few earlier studies have demonstrated the status of lipid peroxidation and antioxidant defense mechanism in plasma and erythrocytes of oral cancer [7][8][9][10], there are no reports on lipid peroxidation and antioxidant therapy in patients with leukoplakia in a specific sub-group of tobacco abusers. Against this background, a prospective study with control was carried out in tobacco abusers:…”
Section: Introductionmentioning
confidence: 99%